ASSET Theoretical Lexicon: An agroecology lexicon - Helmer, Thierry; Roche, Mathieu; Martin, Pierre; Enten, François; Reynaud, Lucie; Lebret, Marie-Christine; Bienabe, Estelle; Blanchard, Melanie; Ehrensperger, Albrecht; Hernandez Barco, Ricardo Alfonso; Priour, Germain (2023)
The overall objective of the ASSET Project is to transform food and agricultural systems in Southeast Asia more sustainable, safer and inclusive, through harnessing the potential of Agroecology. In this context, working groups were organized in order to build a lexicon composed by 16 concepts with 331 terms dealing with Agroecology. This lexicon could be used for the knowledge hub associated with the ASSET Project. In November 2022, 3 workshops were organized in Cambodia, Laos and Vietnam to validate these terms. This dataset contains: - A presentation that summarizes the methods (i‧e. expertise, text-mining) and sources (i‧e. Agrovoc, dicoAE) used to construct this theoretical lexicon (TL) - A presentation that details how this kind of lexicon is used with KEOPS - The agroecology theoretical lexicon (TL) with terms validated (2023-01-09)